CdO Doped CuO for Gas Sensing Environmental Applications - Mohammad Arqam (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper describes the hydrothermal synthesis of cadmium/copper oxide nanocomposite (CdO-CuO). XRD, FESEM, and EDS were used to determine the structure, morphology and compositional. Furthermore, the LPG sensing capabilities of pure and CdO doped CuO were investigated. The sensors had sensitivity of about 24 and 36 at 275oC operating temperature and 250 ppm gas concentration. LPG is extremely flammable even at very low ppm concentrations; detecting LPG low ppm concentrations is needed for security reasons.